Insecticides Pollution on the Three Water Birds Species (Little Black Cormorant, Little Egret and Javan Pond Heron) in Rice-Field at Sukamandi, Subang, West Java - Lin Nuriah Ginoga (Department of Forest Resources Conservation and Ecotourism - IPB University, 2005)
Significant use of insecticide in rice-field by intensification program can directly endanger the environment and sustainability of birds living in the habitat. The objective of the investigation is to study negative impact of insecticide pollution on rice-field environment and on water birds. The research has been conducted on : (1) the diversity of vegetation and macrozoobenthos; (2) insecticide content in water, soil, food, eggs, and tissues of the three water birds species namely little black cormorant, little egret and javan pond heron; and (3) community utilization of insecticide. The research was carried out in Sukamandijaya Village, Ciasem district, under Subang Regency. Samples of eggs and birds were taken from the Sukamandi Rice Research Institute. Purposive sampling application was used in the survey method. The vegetation characteristics in research site include 5 species of weeds in the rice-field and 15 species of weeds in the rice-field dike are also studied. Macrozoobenthos was taken in 20 sampling location consisted of 17 types. Diversity index ranged from 0.469 to 2.689, and water quality of irrigation range from light to high levels pollution. Laboratory analysis were able to detect the presence of 9 types of insecticides consisted of 3 groups, namely : (1) organochlorine (BHC, Aldrin, Endosulfan, Dieldrin, DDT, and Endrin); (2) organophosphat (Chlorpirifos and Diazinon); and (3) Carbamat (Carbofuran). The lowest concentration of insecticide was found in the water, while highest was in the fat tissues of birds. Although the local community recently used only organochlorine (Endosulfan) and other 5 insecticide belonging to this group were detected in the samples. Another group of insecticide used by the community, pirethroid, was not detected in the samples. Results of research further indicated the occurrence of biomagnification starting from the water , soil, food, eggs, and tissues.